Simuliranje izotermnega QUEOS preskusa mešalne faze eksplozije pare Q08 - Leskovar, Matjaž (Strojniški vestnik, 2002)
The premixing phase of a steam explosion covers the interaction of the melt jet with the water prior to any steam explosion occuring. To ger a better insight into the hydrodynamic processes during the premixing phase in addition to "hot" premixing experiments, where the water evaporation is significant. "cold" isothermal premixing experiments were also performed. The special feature of isothermal premixing experiments is that three phases are involved - the water, the air and the spheres phase - but only the spheresphase mixes with the other two phases, whereas the water and air phases do not mix and remain separated by a free surface. Our idea was to treat the isothermal premixing process with an original, combined multiphase model. In the developed combined multiphase model the water and air phases are treatied with a free-surface model as a single joint phase with discontinious phase properties at the water-air interface. The spheres are treated, as a usual, with a multiphase flow model, where the spheres representthe dispersed phase and the joint water-air phase represents the continuous phase. ...
Keywords: tok večfazni; modeli večfazni; eksplozija pare; metode z nivojsko funkcijo; simuliranje; večfazni tok; para; eksplozije; modeliranje; simulacije